Formation of Six Sigma Infrastructure for the Coronary Stenting Process - Taner, Mehmet Tolga; Kagan, Gamze; Celik, Sezai; Erbas, Engin; Kagan, Mehmet Kemal (International Review of Management and Marketing, 2013)
The purpose of this study is to show how a tertiary care center in Turkey operating mainly in cardiology initiated Six Sigma principles to reduce the number of complications occuring during coronary stent insertion process. A Six Sigma’s Define-Measure-Analyze-Improve-Control (DMAIC) model for coronary stent insertion is suggested. Data were collected for 24-months. Twenty-two Critical-to-Quality (CTQ) factors were identified for successful coronary stent insertion. The most frequent causes of complications in the process were found to be patients with previous bypass surgery or PCI, inexperience of staff members, highly damaged vessel structure, thin and/or long vessel diameter, inappropriate selection of stent type, inappropriate selection of balloon type and poor image quality. Keywords: Six Sigma; cardiology; stent insertion; complications JEL Classifications: I120; L15